Indian Phenotype Characteristics Among Patients with Type 2 Diabetes Mellitus: Insights from a Non-interventional Nationwide Registry in India. (June 2022) - Kalra, Sanjay; Mithal, Ambrish; Zargar, Abdul Hamid; Sethi, Bipin; Dharmalingam, Mala; Ghosh, Sujoy; Sen, Ranjini
No abstract available